Stability of Nonlinear Fractional Neutral Differential Difference Systems - Kewei Liu; Wei Jiang (Discrete Dynamics in Nature and Society)
We study the stability of a class of nonlinear fractional neutral differential difference systems equipped with the Caputo derivative. We extend Lyapunov-Krasovskii theorem for the nonlinear fractional neutral systems. Conditions of stability and instability are obtained for the nonlinear fractional neutral systems.